Behaviour of cell penetrating peptide TAT-modified liposomes loaded with salvianolic acid B on the migration, proliferation, and survival of human skin fibroblasts. (2nd January 2020) - Shi, Jun; Guo, Siyi; Wu, Yanting; Chen, Guitian; Lai, Jianhui; Xu, Xiaoqi
Abstract: To investigate the efficacy of cell penetrating peptide TAT-modified liposomes loaded with salvianolic acid B (SAB-TAT-LIP) on the proliferation, migration, survival, and TGF-β1 expression of human skin fibroblasts (HSF) and to preliminarily evaluate its effect on the prevention and treatment of hypertrophic scars. SAB-TAT-LIP was prepared using the pH gradient reverse-phase evaporation method. The properties of the liposomes including morphology, percent entrapment efficiency, mean diameter, polydispersity index (PDI), zeta potential, in vitro release, in vitro percutaneous absorption, and serum stability were studied. The proliferation of HSF cells was examined by MTT assays. Cell migration was assessed using the transwell and scratch assays. Cell cycle status was assessed by flow cytometry. Apoptotic induction was assessed through Annexin V-FITC/PI staining. The entrapment efficiency of SAB-TAT-LIP was 86.70 ± 0.85% and the salvianolic acid B (SAB) displayed a unimodal size-distribution with a mean diameter of 183.2 nm ± 4.09, a PDI of 0.190, and a zeta potential of −9.25 mV ± 0.92. The in vitro cumulative release of SAB-TAT-LIP was 62.49% after 24 h. The in vitro 32 h cumulative transdermal rate was 17.21% and the dermal retention was 44.39 μg/cm 2 ±6.87. SAB-TAT-LIP inhibited HSF proliferation in a concentration and time-dependent mode and inhibited the migration and invasion of HSF cells. SAB-TAT-LIP also significantly increased apoptotic induction, the number cells in the G0/G1 phase of the cell cycle, and decreased the levels of TGF-β1 after 48 h of treatment relative to the control group ( p < 0.05, p < 0.01). SAB-TAT-LIP offers a promising therapeutic strategy for transdermal delivery during the prevention and treatment of HS.